Treatment of San Mateo sanitary landfill leachate using a biofilm reactor with unwoven polyester fiber support material - Uy, Richard Bryan Cabarios (2002)
The performance of an aerobic fixed-film bioreactor utilizing unwoven polyester fiber as support material in treating landfill leachate from the San Mateo Sanitary Landfill was investigated. Reactor performance was based on biomass retention and, organic and nitrogen removal. The effect of hydraulic retention time (HRT) on the performance of the fixed-film reactor was also studied. HRT of 10, 18, and 24 hours were investigated.